Remarriage After Divorce: A Theological, Sociological, And Psychological Study Of The Suitability Of Church Ministry - Sarma Marpaung; Adi Prasetyo Wibowo; Tjutjun Setiawan (LPPM Universitas PGRI Sumatera Barat, 2020)
The phenomenon of divorce and remarriage among Christians raises theological, sociological, and psychological questions regarding a person's suitability to serve in church offices, particularly pastoral offices. This study uses a descriptive qualitative approach through a literature study, examining key biblical texts such as Matthew 5:32, Matthew 19:9, Mark 10:11–12, and Romans 7:2–3, as well as theological literature, family sociology, and pastoral psychology [. Biblically, most texts affirm permanent monogamous fidelity, while arguments for remarriage emphasize grace, restoration, and the cultural context of Jesus' time. From a sociological and psychological perspective, divorce and remarriage impact emotional stability, family relationships, and the quality of church ministry. The study's conclusion emphasizes that the church needs to uphold the truth of God's word normatively, while providing a path of restoration for those who sincerely repent.